Associations between attainment of incentivised primary care diabetes indicators and mortality in an English cohort. (April 2021) - McKay, Ailsa J.; Gunn, Laura H.; Vamos, Eszter P.; Valabhji, Jonathan; Molina, German; Molokhia, Mariam; Majeed, Azeem
Abstract: Aims: To describe associations between incentivised primary care clinical and process indicators and mortality, among patients with type 2 diabetes in England. Methods: A historical 2010–2017 cohort (n = 84, 441 adults) was derived from the UK CPRD. Exposures included English Quality and Outcomes Framework glycated haemoglobin (HbA1c; 7.5%, 59 mmol/mol), blood pressure (140/80 mmHg), and cholesterol (5 mmol/L) indicator attainment; and number of National Diabetes Audit care processes completed, in 2010–11. The primary outcome was all-cause mortality. Results: Over median 3.9 (SD 2.0) years follow-up, 10, 711 deaths occurred. Adjusted hazard ratios (aHR) indicated 12% (95% CI 8–16%; p < 0.0001) and 16% (11–20%; p < 0.0001) lower mortality rates among those who attained the HbA1c and cholesterol indicators, respectively. Rates were also lower among those who completed 7–9 vs. 0–3 or 4–6 care processes (aHRs 0.76 (0.71–0.82), p < 0.0001 and 0.61 (0.53–0.71), p < 0.0001, respectively), but did not obviously vary by blood pressure indicator attainment (aHR 1.04, 1.00–1.08; p = 0.0811). Conclusions: Cholesterol, HbA1c and comprehensive process indicator attainment, was associated with enhanced survival. Review of community-based care provision could help reduce the gap between indicator standards and current outcomes, and in turn enhance life expectancy.